2016
DOI: 10.1371/journal.pone.0156260
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-1301-Mediated RanGAP1 Downregulation Induces BCR-ABL Nuclear Entrapment to Enhance Imatinib Efficacy in Chronic Myeloid Leukemia Cells

Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative disease. Imatinib (IM), the first line treatment for CML, is excessively expensive and induces various side effects in CML patients. Therefore, it is essential to investigate a new strategy for improving CML therapy. Our immunoblot data revealed that RanGTPase activating protein 1 (RanGAP1) protein levels increased by approximately 30-fold in K562 cells compared with those in normal cells. RanGAP1 is one of the important components of RanGTPase system, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Fang et al ( 35 ) concluded that miR-1301-3p may function as an inhibitor of tumorigenesis, regulating cell apoptosis through B-cell lymphoma-2 (Bcl-2) and Bcl-xL in hepatocellular carcinoma HepG2 cells. Lin et al ( 36 ) indicated that miR-1301-3p-induced downregulation of Ran GTPase activating protein 1 may activate the p73-dependent apoptosis pathway by mediating breakpoint cluster region-Abelson tyrosine-protein kinase nuclear entrapment, which, may be a novel strategy for improving the current Imatinib treatment for chronic myeloid leukemia. Another study demonstrated that miR-1301-3p was upregulated in prostate cancer cells and tissues ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al ( 35 ) concluded that miR-1301-3p may function as an inhibitor of tumorigenesis, regulating cell apoptosis through B-cell lymphoma-2 (Bcl-2) and Bcl-xL in hepatocellular carcinoma HepG2 cells. Lin et al ( 36 ) indicated that miR-1301-3p-induced downregulation of Ran GTPase activating protein 1 may activate the p73-dependent apoptosis pathway by mediating breakpoint cluster region-Abelson tyrosine-protein kinase nuclear entrapment, which, may be a novel strategy for improving the current Imatinib treatment for chronic myeloid leukemia. Another study demonstrated that miR-1301-3p was upregulated in prostate cancer cells and tissues ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Imatinib-resistant CML K562 cells (K562-RC and K562-RD cells), the oncomiRs miR-21 and miR-26b were upregulated and the tumor suppressor miR-451 was downregulated in comparison with sensitive cells [ 180 ]. Other mi-RNAs, such as miR-19a, miR-19b, miR-17, miR-130, and miR-150, are increased in CML [ 181 , 182 ]. The expression of some of these miRs is directly regulated by BCR-ABL1 through its effect on miR effectors, such as MYC in the case of miR-17 [ 183 ], CCN3 in the case of miR-130 [ 184 ], and MYB in the case of miR-150 [ 176 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…miR-1301 is involved in human cancers but shows an ambiguous behavior ( 450 , 451 ). It can target the Ran GTPase Activating Protein 1 (RanGAP1) mRNA, as demonstrated by inverse correlation in CML patients: the RanGAP1 protein down-regulation or an increased miR-1301 are beneficial for the sensitivity to imatinib ( 452 ). miR-7 acts as an inhibitor in hepatocellular and pancreatic carcinomas ( 453 , 454 ) possibly regulating the PI3K/AKT pathway, which is also downstream of BCR-ABL ( 455 ).…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 99%